2013
DOI: 10.1002/jgrd.50326
|View full text |Cite
|
Sign up to set email alerts
|

Eastern U.S. summer streamflow during extreme phases of the North Atlantic oscillation

Abstract: Numerous studies have suggested streamflow discharge in the conterminous U.S. has been increasing, particularly in the east starting in the latter half of the 20th century. Northern Hemisphere (NH) hydroclimatic variability has been connected to shifts in large‐scale atmospheric teleconnection patterns. This study ascertained the spatial and temporal influences of the extreme phases of the North Atlantic Oscillation (NAO) on interannual streamflow variability across the eastern U.S. during the summer season. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…We recognize that it is more commonplace for hydroclimatic studies that identify a neutral NAO condition to identify larger index thresholds (e.g. ±0.5 or ±1) (Hurrell 2003, Coleman andBudikova 2013). However, our purpose is not to identify high/low, or 'extreme', phases of the NAO.…”
Section: Testing For Nao/enso Linkages With Northeastern Us Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognize that it is more commonplace for hydroclimatic studies that identify a neutral NAO condition to identify larger index thresholds (e.g. ±0.5 or ±1) (Hurrell 2003, Coleman andBudikova 2013). However, our purpose is not to identify high/low, or 'extreme', phases of the NAO.…”
Section: Testing For Nao/enso Linkages With Northeastern Us Floodingmentioning
confidence: 99%
“…However, recent research by Steinschneider and Brown (2011) and Coleman and Budikova (2013) suggest mechanisms by which such gains may be preserved and/or enhanced into the following water year. For example, Steinschneider and Brown (2011) found a positive correlation between the winter NAO phase and late summer one-and seven-day low flow in the Connecticut River basin in New England.…”
Section: Our Findings Lead To Several Important Questionsmentioning
confidence: 99%
“…During high‐NAO winters, the extension of Bermuda/Azores high to the northeastern U.S. blocks the invasion of the polar jet stream and the mid‐latitude winter storms, which results in the decrease in winter precipitation in northeastern U.S. (Ning and Bradley, ) and then alters the streamflow in this region. Coleman and Budikova () found that the NAO, especially the negative phase, can impact the eastern U.S. summer streamflow up to three seasons in advance. During positive NAO years, the southerly wind anomalies induced by the east‐west pressure gradient and the blocked invasion of polar jet stream due to extension of Bermuda/Azores high leads to positive temperature anomalies in the northeastern U.S.…”
Section: Introductionmentioning
confidence: 99%
“…). In the western U.S. and Alaska, the North Atlantic Oscillation and Pacific Decadal Oscillation (PDO) have also been linked to sudden changes in weather which altered streamflow (Woo and Thorne ; Coats ; Coleman and Budikova ). In the southeastern U.S., complex patterns linking different decadal oscillations to seasonal differences in flow have been described, emphasizing the important link between climate and streamflow (Sheldon and Burd ).…”
Section: Resultsmentioning
confidence: 99%